Predicting Women’s Recidivism Using the Dynamic Risk Assessment for Offender Re-Entry: Preliminary Evidence of Predictive Validity With Community-Sentenced Women Using a “Gender-Neutral” Risk Measure - Scanlan, Jessica M. (Criminal justice and behavior, 2020)
Although men and women share risk factors for offending, some scholars suggest these factors operate differently across gender and that women-specific risk factors are neglected in existing “gender-neutral” risk assessment tools. This article explored the predictive validity of one gender-neutral risk assessment tool—the Dynamic Risk Assessment for Offender Re-Entry (DRAOR)—with matched samples of women and men serving community supervision sentences. Total DRAOR scores had comparative predictive validity across gender. For women and men, the DRAOR predicted reconviction over a static risk measure. The findings support the general premise of gender neutrality, but do not necessarily suggest the DRAOR, or gender-neutral tools more broadly, are the best tools for use with women.